Publisher Correction: Neoadjuvant immune checkpoint blockade in high-risk resectable melanoma. (December 2018) - Amaria, Rodabe; Reddy, Sangeetha; Tawbi, Hussein; Davies, Michael; Ross, Merrick; Glitza, Isabella; Cormier, Janice; Lewis, Carol; Hwu, Wen-Jen; Hanna, Ehab; Diab, Adi; Wong, Michael; et al.
In the version of this article originally published, there was an error in Fig. 1. In the neoadjuvant phase column, then values for arms A and B were both reported to be 20. Then values for arms A and B were actually 12 and 11, respectively. Also, the URL underlying the accession code in the data availability section was incorrect. The URL was originally https://www.ebi.ac.uk/ega/studies/EGAS00001002698. It should have been https://www.ebi.ac.uk/ega/studies/EGAS00001003178. The errors have been corrected in the print, HTML and PDF versions of this article.